Customers’ Perception on Banking Communication - Rijal, Rheet (KMC Journal, 2024)
This study explored customers’ perceptions of banking communication in “A” grade banks within Surkhet Valley, Nepal, aiming to fill a critical gap in understanding the dynamics of communication within the banking sector. Drawing upon existing literature and theoretical frameworks, the research investigated factors influencing customer awareness and satisfaction regarding banking communication. Through a quantitative approach involving 405 respondents, the study employed ordered logistic regression analysis to discern significant relationships between various demographic and experiential factors and banking communication awareness levels. Findings revealed that age, participation in common schemes, hassle with account updates, involvement with ASWA (Automated Settlement of Withdrawals and Advances), gender and work experience significantly impacted banking communication awareness levels among customers. Age, common scheme participation, hassle with account updates and ASWA involvement positively influence awareness and gender and work experience exhibited negative associations. These results underscored the importance of tailored communication strategies targeting diverse demographic groups to enhance overall banking communication effectiveness. The implications extend to managerial practices, suggesting the adoption of transparent and accessible communication channels, and policy recommendations aimed at promoting regulatory frameworks conducive to improved customer engagement. Furthermore, the study highlighted avenues for future research, including the exploration of cultural and regional influences on banking communication perceptions. By addressing the identified factors, banks can strengthen customer relationships, foster loyalty and enhance service quality, thereby contributing to the sustainable growth of the banking sector in Surkhet Valley.